MicroRNA as an Early Biomarker of Neonatal Sepsis - Jouza, Martin; Bohosova, Julia; Stanikova, Andrea; Pecl, Jakub; Slaby, Ondrej; Jabandziev, Petr (Frontiers in Pediatrics, 2022)
Sepsis is a major cause of lethality in neonatal intensive care units. Despite significant advances in neonatal care and growing scientific knowledge about the disease, 4 of every 10 infants born in developed countries and suffering from sepsis die or experience considerable disability, including substantial and permanent neurodevelopmental impairment. Pharmacological treatment strategies for neonatal sepsis remain limited and mainly based upon early initiation of antibiotics and supportive treatment. In this context, numerous clinical and serum-based markers have been evaluated for diagnosing sepsis and evaluating its severity and etiology. MicroRNAs (miRNAs) do not encode for proteins but regulate gene expression by inhibiting the translation or transcription of their target mRNAs. Recently, it was demonstrated in adult patients that miRNAs are released into the circulation and that the spectrum of circulating miRNAs is altered during various pathologic conditions, such as inflammation, infection, and sepsis. Here, we summarize current findings on the role of circulating miRNAs in the diagnosis and staging of neonatal sepsis. The conclusions point to substantial diagnostic potential, and several miRNAs have been validated independently by different teams, namely miR-16a, miR-16, miR-96-5p, miR-141, miR-181a, and miR-1184.